Analysis of strategic potential and development of strategies for an industrial enterprise: a practical study on the example of Davos-Trading LLC ("Journal "U". Economy. Management. Finance.", 2025)
The article considers the analysis of strategic potential and development of strategies for an industrial enterprise, performed on the example of Davos-Trading LLC. Three key stages were identified within the framework of the study: analysis of the internal environment, analysis of the external environment and formation of strategic alternatives. At the first stage, the key internal resources and competencies of the company that ensure its competitiveness in the industry, as well as the effectiveness of existing strategies, were assessed. The strengths and weaknesses of the enterprise were identified, measures were proposed to strengthen the internal potential for sustainable growth. At the second stage, an analysis of external factors, such as industry trends, macroeconomic conditions and competitive threats was carried out, which made it possible to determine the opportunities and risks for the company. The third stage includes the development of strategic alternatives taking into account the data obtained, an assessment of their sustainability and long-term impact on the development of the company. The main conclusion of the work is the proposal of an optimal strategy for Davos-Trading LLC aimed at strengthening the strategic potential of the enterprise in the face of external and internal challenges. The article is a comprehensive approach to managing the strategy of an industrial enterprise and provides recommendations for increasing its competitiveness.
Keywords: strategic potential; industrial enterprise; strategic alternatives; internal analysis of industrial enterprise; external analysis of industrial enterprise; strategy management